HUBUNGAN CACAT KONGENITAL DENGAN KEJADIAN SKIZOFRENIA USIA DIBAWAH 25 TAHUN - Dhian Ika Prihananto; Muhammad Mudzakkir; Susi Ernawati (Universitas Pesantren Tinggi Darul Ulum, 2022)
Schizophrenia is a disease that affects the brain and causes strange and disturbed thoughts, perceptions, emotions, movements, and behaviors. Schizophrenia mental disorder does not just happen by itself, however, there are many factors that cause schizophrenia. The factors that cause schizophrenia are somatogenic, psychogenic, sociogenic factors. Including somatogenic factors, namely heredity, congenital defects, brain abnormalities, temperament, disease and bodily injury. The purpose of this study was to determine the relationship between congenital defects and the incidence of schizophrenia under the age of 25 years. This research is a mixed method research, case-control study design. The study population is sufferers and families with schizophrenia under the age of 25 in the Kepil sub-district, Wonosobo district. The sample consisted of 55 cases and 55 controls which were taken by consecutive sampling. The research instrument was an interview questionnaire. Data analysis was univariate, bivariate (chi-square). The results showed that 1 respondent (1.8%) had congenital defects in the case group and 1 respondent (1.8%) in the control group. The results of the bivariate test (chi-square) obtained p = 1.000 OR = 1.000 95% CI = 0.061-16.401. The conclusion is that there is no relationship between congenital defects and the incidence of schizophrenia under the age of 25 years. Keywords: Congenital defects, Schizophrenia, Age under 25 years